An investigation on gamma-ray shielding properties of quaternary glassy composite (Na2Si3O7/Bi2O3/B2O3/Sb2O3) by BXCOM and MCNP 6.2 code - Akcali, Ozgur; Caglar, Mustafa; Toker, Ozan; Bilmez, Bayram; Kavanoz, H. Birtan; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Analytic and stochastic methods were proposed for the determination of gamma-ray radiation shielding properties of the glassy composites. Radiation shielding properties such as mass attenuation coefficients, effective atomic numbers, effective electron numbers, build-up factors (exposure build-up factors and energy absorption build-up factors) can be determined with these techniques. A versatile quaternary composite was studied with different mass ratios in order to optimize the gamma radiation attenuation. Exposure build-up factors (EBFs), energy absorption build-up factors (EABFs), effective atomic numbers (Z(eff)) and effective electron densities (N-eff) were calculated via BXCOM. Furthermore, MCNP transport code, version of 6.2, was used to simulate the mass attenuation coefficients (mu/rho) and the half-value layers (HVLs) of the composites. Since they are compatible, simulation and BXCOM results denote that these methods can be used to determine the radiation shielding parameters for the glassy composites for which there are no satisfactory experimental values available. All in all, the optimum mass ratio, having the highest radiation attenuation, was determined as [Na2Si3O7/Bi2O3(65/35)/B2O3(2)/Sb2O3(11)], so that glassy composite might be preferred as a radiation shield in various applications. The quaternary glassy composites investigated in this study, performs better than ordinary concrete, getting close to pure lead as a radiation shield.
Keywords: Build-up factors; BXCOM; Glassy composites; MCNP 6.2; EXPOSURE BUILDUP FACTORS; ATTENUATION-COEFFICIENT; STRUCTURAL-PROPERTIES; ENERGY-ABSORPTION; BORATE; EFFICIENCY; BARIUM; BI2O3; OXIDE; Nuclear Science & Technology